Visuospatial working memory interference with recollections of trauma. - Lilley, SA; Andrade, J; Turpin, G; Sabin-Farrell, R; Holmes, E (2009)
OBJECTIVES: Laboratory research using a working memory framework has shown modality-specific reductions in image vividness and emotionality when concurrent tasks are performed while maintaining the image in consciousness. We extended this research to trauma images in a clinical population awaiting treatment for post-traumatic stress symptoms. DESIGN: A within-subjects design was used, with each participant completing an imagery task under three concurrent task conditions: side-to-side eye-movements, counting, and exposure only (no concurrent task). METHODS: Eighteen participants selected three images each, the images being those that were the most distressing from participants' trauma memories and most likely to intrude involuntarily. Participants gave baseline ratings of the vividness and emotionality of each of their trauma images. Each image was assigned to a condition. Each condition comprised 8 trials in which participants recollected the appropriate image for 8 s while performing eye-movements, counting or no concurrent task, and then rated its vividness and emotionality. Follow-up ratings were obtained by telephone 1 week later. RESULTS: The eye-movement task reduced vividness and emotionality of the trauma images relative to the counting task and exposure only, but did so only during the imagery period and not at follow-up. The images were predominantly visual. CONCLUSIONS: Concurrent tasks matched to the modality of trauma images may provide a useful treatment aid for temporarily dampening emotional responses to recollections of trauma.